Rose residue activated carbon and its preparation method and application
By preparing rose residue activated carbon, the problem of rose residue utilization and the problem of low efficiency in dye wastewater treatment are solved, and efficient recycling and utilization of adsorbed dyes and resources are achieved.
Patent Information
- Application Number
- CN202410159862.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-04
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-02-04
AI Technical Summary
The prior art is difficult to effectively utilize rose residue, and the treatment efficiency of dye wastewater is low, resulting in environmental pollution.
Rose residue activated carbon with adsorption properties was prepared by carbonizing the dried rose residue at 230-250°C, then impregnating in an activator and activating in a high-temperature muffle furnace. Finally, after pickling, water washing and drying, rose residue activated carbon with adsorption properties was prepared. .
Rose residue activated carbon can efficiently adsorb dyes in wastewater, especially methylene blue, with a removal rate of up to 99%, reducing resource waste and improving the economic benefits of the rose industry.
Smart Images

Figure CN118083974B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dye wastewater treatment, and in particular relates to rose residue activated carbon and a preparation method and application thereof. Background Art
[0002] Roses are planted in many provinces in my country because of their great value. One of the main uses is to extract rose essential oil. Due to the limitations of rose essential oil extraction technology in roses, the oil yield of roses is very low. Therefore, in order to extract rose essential oil to meet market demand, a large amount of roses are needed, resulting in a large amount of accumulation of rose residues, a byproduct of rose essential oil extraction. At present, the effective utilization technology of rose residues in my country is still immature, and the main research is still in food processing. However, existing data show that the application of rose residues in food is mostly in the research stage, and due to the presence of rose pigments in rose residues and the interference of various fragrances in roses, the utilization of rose residues is not sufficient. There is a study that uses rose residues as raw materials to produce laccase by liquid fermentation using Pycnoporus sp.W-9 strains. The obtained laccase is used for phenol degradation, and the removal rate of phenol can reach 86.6%, which shows that the use of rose residues has a certain function of adsorbing and degrading pollutants.
[0003] With the continuous expansion of the printing and dyeing industry at home and abroad, the discharge of printing and dyeing wastewater has increased significantly. In particular, methylene blue is used in various industrial processes such as textiles, papermaking, wool, plastics, cosmetics and pharmaceutical products. The direct discharge of untreated dye wastewater causes great pollution and harm to the environment. Removing dyes from wastewater has attracted widespread attention. Summary of the invention
[0004] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a rose dregs activated carbon.
[0005] Another object of the present invention is to provide a rose flower residue activated carbon rod prepared from the rose flower residue activated carbon.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned rose dregs activated carbon and rose dregs activated carbon rods.
[0007] Another object of the present invention is to provide the rose dregs activated carbon and rose dregs activated carbon rods for use in removing dyes from wastewater.
[0008] The present invention is achieved by a method for preparing rose dregs activated carbon, the method comprising the following steps:
[0009] (1) carbonizing the dried rose flower residue at 230-250° C. for 6-8 min to obtain a carbon precursor;
[0010] (2) impregnating the carbon precursor in an activator for 3 to 5 hours to obtain an impregnation solution;
[0011] (3) adding the impregnation liquid into a high-temperature muffle furnace preheated to 390-410° C., heating the temperature to an activation temperature of 490-510° C. at a rate of 9-11° C. / min, maintaining the activation temperature for 45-55 min, then taking out and cooling to room temperature to obtain an activated product;
[0012] (4) The activated product is sequentially acid-washed, water-washed and dried to obtain rose residue activated carbon.
[0013] Preferably, in step (1), the dried rose flower residue is carbonized at 240° C. for 7 min to obtain a carbon precursor;
[0014] In step (2), the activator is potassium hydroxide with a mass concentration of 20%, and the impregnation ratio of the carbon precursor in the activator is 1:1.
[0015] Preferably, in step (3), the impregnation liquid is added to a high-temperature muffle furnace preheated to 400°C, heated to an activation temperature of 500°C at a rate of 10°C / min, maintained at the activation temperature for 50 minutes, then taken out and cooled to room temperature to obtain an activated product.
[0016] Preferably, in step (4), the acid washing is to use a hydrochloric acid solution with a mass concentration of 10% until no reaction occurs after the addition of the acid; the water washing is to use water until the outflowing water is transparent and colorless; the drying is to dry at 110°C for 3 hours, then take out and cool to room temperature.
[0017] The invention further discloses rose residue activated carbon prepared by the method.
[0018] The present invention further discloses a method for preparing a rose slag activated carbon rod, which comprises the following steps:
[0019] (1) After coating the etched stainless steel wire surface with polyimide sealing resin, the rose slag activated carbon is quickly and evenly coated on the stainless steel wire surface;
[0020] (2) Aging the stainless steel wire coated in step (1) at 240-260° C. for 1-3 h to obtain a rose slag activated carbon rod.
[0021] Preferably, in step (1), the stainless steel wire is immersed in a hydrofluoric acid solution with a mass concentration of 40%, etched at 70° C. for 10 min, and cleaned alternately with ultrapure water and anhydrous ethanol to obtain a stainless steel wire with a rough surface after etching.
[0022] The invention further discloses a rose residue activated carbon rod prepared by the method.
[0023] The present invention further discloses the application of the rose residue activated carbon or rose residue activated carbon rod in adsorbing wastewater dyes; wherein the dyes include methylene blue, methyl orange, rhodamine B, malachite green and crystal violet.
[0024] Preferably, the dye is methylene blue.
[0025] The present invention overcomes the deficiencies of the prior art and provides a rose dregs activated carbon and a preparation method and application thereof. The present invention carbonizes the dried rose dregs at 230-250°C for 6-8 minutes to obtain a carbon precursor; the carbon precursor is impregnated in an activator for 3-5 hours to obtain an impregnation liquid; the impregnation liquid is added to a high-temperature muffle furnace preheated to 390-410°C, and the temperature is raised to an activation temperature of 490-510°C at a rate of 9-11°C / min, and the activated product is taken out and cooled to room temperature after being kept at the activation temperature for 45-55 minutes; the activated product is sequentially acid-washed, water-washed and dried to obtain rose dregs activated carbon. In the present invention, when rose dregs activated carbon solid powder enters the mixed dye aqueous solution, surface charge will be generated, and this surface charge comes from the dissociation of rose dregs activated carbon surface groups or the adsorption of ions in the solution and the pH value of the aqueous solution, wherein the negative charge is generated by the dissociation of surface oxygen acidic complexes such as carboxyl and phenolic groups, and the positive charge may be the basic characteristic of the surface oxygen complex, and the surface charge of rose dregs activated carbon will affect the adsorption of dye molecules. The adsorption of rose dregs activated carbon to mixed dye molecules is correlated with the initial pH value, the interaction between each dye molecule, and the interaction between π-π bonds. Under the joint action of various factors, rose dregs activated carbon has a good adsorption effect on methylene blue, malachite green, crystal violet, rhodamine B, and methyl orange dye molecules in the mixed dye molecules.
[0026] Compared with the shortcomings and deficiencies of the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention recycles rose dregs to prepare activated carbon with adsorption performance, thereby reducing waste of resources and improving the economic and social benefits of the rose industry.
[0028] (2) The adsorption of methylene blue by rose residue activated carbon includes both chemical adsorption and physical adsorption, and there is both monomolecular layer adsorption and multimolecular layer adsorption.
[0029] (3) From the single factor experimental analysis of the adsorption of methylene blue solution by rose residue activated carbon, it was found that the removal rate of methylene blue was the highest when the initial concentration of methylene blue was 80 mg / L, the dosage of rose residue activated carbon was 0.15 g, and the initial pH was 11, reaching 99%.
[0030] (4) Through the Box-Behnken central composite experimental design, it was found that when the initial concentration of methylene blue and the dosage of rose residue activated carbon acted together, the removal rate of methylene blue was most significantly affected. The degree of influence was in descending order: the dosage of activated carbon, methylene blue concentration, and initial pH.
[0031] (5) The rose slag activated carbon prepared with rose slag as raw material and potassium hydroxide as activator shows obvious pore structure on the surface, and the pore shape is a neatly arranged honeycomb structure. The average pore size of the rose slag activated carbon is 4.2nm, and the total pore volume is 0.1589cm 3 / g, mesopores account for 54.05%, mainly mesopore structure, while there are a small amount of micropores and macropores. From the FTIR spectrum, the functional groups contained in rose slag activated carbon are mainly carboxyl and carbonyl hydrophilic groups, which are conducive to the adsorption reaction.
[0032] (6) Although the rose dregs activated carbon of the present invention has a high dye adsorption efficiency, the use of powdered activated carbon in large-scale adsorption is limited due to the difficulty in separation and recovery by filtration or centrifugation. Therefore, the present invention further prepares rose dregs activated carbon rods for removing pollutants such as dyes and colorants in wastewater or intermediate solutions, which is more practical. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a conversion morphology diagram of rose slag activated carbon material 1 and rose slag activated carbon rod 1;
[0034] Figure 2 is the adsorption kinetics fitting curve; in the figure, curve 1, pseudo-first-order kinetic model; curve 2, pseudo-second-order kinetic model;
[0035] Figure 3 is the isothermal adsorption model fitting curve; in the figure, curve 1, Langmuir adsorption model; curve 2, Freundlich adsorption model;
[0036] Figure 4 It is the recycling of rose slag activated carbon;
[0037] Figure 5 is the effect of initial concentration on the removal of methylene blue over time;
[0038] Figure 6 is the effect of activated carbon dosage on methylene blue removal rate over time;
[0039] Figure 7 is the effect of solution pH on the removal rate of methylene blue over time;
[0040] Figure 8 is the comparison between the measured value and the predicted value of methylene blue removal rate;
[0041] Fig. 9 It is the effect of the interaction between initial concentration and dosage on the removal rate of methylene blue; among them, the left figure: the response surface diagram of the interaction between initial concentration and dosage on the removal rate of methylene blue, the right figure: the contour diagram of the interaction between initial concentration and dosage on the removal rate of methylene blue;
[0042] Fig.10 The figure below is the effect of the interaction between pH and dosage on the removal rate of methylene blue. The left figure shows the response surface diagram of the interaction between pH and dosage on the removal rate of methylene blue. The right figure shows the contour diagram of the interaction between pH and dosage on the removal rate of methylene blue.
[0043] Fig.11 The effect of the interaction between initial concentration and pH on the removal rate of methylene blue; the left figure: the response surface diagram of the interaction between initial concentration and pH on the removal rate of methylene blue, the right figure: the contour diagram of the interaction between initial concentration and pH on the removal rate of methylene blue;
[0044] Fig.12 is the N2 adsorption-desorption isotherm and pore size distribution diagram;
[0045] Fig.13 This is the SEM microscopic morphology of rose dregs and their activated carbon;
[0046] Fig.14 This is the EDX analysis of rose slag activated carbon;
[0047] Fig.15 This is the XRD of rose slag activated carbon;
[0048] Fig.16 This is the FTIR spectrum of rose flower residue activated carbon. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0050] In the following examples, rose residue comes from the residue left after a rose industry company in Gansu extracts essential oil from roses. Potassium hydroxide, hydrochloric acid, methylene blue, etc. are preferably analytical grade, and the water used in the experiments is preferably deionized water.
[0051] Example 1
[0052] (1) carbonizing the dried rose flower residue at 240° C. for 7 min to obtain a carbon precursor;
[0053] (2) impregnating the carbon precursor in an activator for 4 hours to obtain an impregnation solution; wherein the activator is potassium hydroxide with a mass concentration of 20%, and the impregnation ratio of the carbon precursor in the activator is 1:1;
[0054] (3) adding the impregnation liquid into a high-temperature muffle furnace preheated to 400° C., heating the temperature to an activation temperature of 500° C. at a rate of 10° C. / min, maintaining the activation temperature for 50 min, then taking the liquid out and cooling it to room temperature to obtain an activated product;
[0055] (4) The activated product was acid-washed with a hydrochloric acid solution having a mass concentration of 10% until no reaction occurred after the addition of the acid, and then washed with water until the outflowing water was transparent and colorless. Finally, it was placed in an oven and dried at 110° C. for 3 h to obtain rose residue activated carbon 1.
[0056] Example 2
[0057] (1) carbonizing the dried rose flower residue at 230° C. for 6 min to obtain a carbon precursor;
[0058] (2) impregnating the carbon precursor in an activator for 3 hours to obtain an impregnation solution; wherein the activator is potassium hydroxide with a mass concentration of 15%, and the impregnation ratio of the carbon precursor in the activator is 1:2;
[0059] (3) adding the impregnation liquid into a high-temperature muffle furnace preheated to 400° C., heating the temperature to an activation temperature of 510° C. at a rate of 11° C. / min, maintaining the activation temperature for 55 min, then taking the liquid out and cooling it to room temperature to obtain an activated product;
[0060] (4) The activated product was acid-washed with a hydrochloric acid solution having a mass concentration of 10% until no reaction occurred after the addition of the acid, and then washed with water until the outflowing water was transparent and colorless. Finally, it was placed in an oven and dried at 110° C. for 3 h to obtain rose residue activated carbon 2.
[0061] Example 3
[0062] (1) carbonizing the dried rose flower residue at 250° C. for 8 min to obtain a carbon precursor;
[0063] (2) impregnating the carbon precursor in an activator for 5 hours to obtain an impregnation solution; wherein the activator is sodium hydroxide with a mass concentration of 20%, and the impregnation ratio of the carbon precursor to the activator is 1:1;
[0064] (3) adding the impregnation liquid into a high-temperature muffle furnace preheated to 390° C., heating the temperature to an activation temperature of 490° C. at a rate of 9° C. / min, maintaining the activation temperature for 45 min, then taking the liquid out and cooling it to room temperature to obtain an activated product;
[0065] (4) The activated product was acid-washed with a hydrochloric acid solution having a mass concentration of 10% until no reaction occurred after the addition of the acid, and then washed with water until the outflowing water was transparent and colorless. Finally, it was placed in an oven and dried at 110° C. for 3 h to obtain rose residue activated carbon 3.
[0066] Example 4
[0067] (1) A stainless steel wire (1.0 cm*0.2 cm) was immersed in a hydrofluoric acid solution with a mass concentration of 40%, and after etching at 70° C. for 10 min, it was cleaned alternately with ultrapure water and anhydrous ethanol to obtain a rough surface with a certain diameter; a polyimide sealing resin was coated on the etched surface of the stainless steel wire, and the wire was quickly rolled back and forth on a weighing paper containing the rose dregs activated carbon material 1 prepared in Example 1, so that the rose dregs activated carbon material was evenly coated on the surface of the stainless steel wire;
[0068] (2) The rose slag activated carbon-coated stainless steel wire prepared in step (1) is aged at 250° C. for 2 h to remove small molecular impurities adsorbed in the material, thereby obtaining a rose slag activated carbon rod 1.
[0069] The transformation between the rose slag activated carbon material 1 and the rose slag activated carbon rod 1 is as follows: Figure 1 shown.
[0070] Example 5
[0071] (1) A stainless steel wire (1.0 cm*0.2 cm) was immersed in a hydrofluoric acid solution with a mass concentration of 40%, and after etching at 70° C. for 10 min, it was cleaned alternately with ultrapure water and anhydrous ethanol to obtain a rough surface with a certain diameter; a polyimide sealing resin was coated on the etched surface of the stainless steel wire, and the wire was quickly rolled back and forth on a weighing paper containing the rose dregs activated carbon material 1 prepared in Example 1, so that the rose dregs activated carbon material was evenly coated on the surface of the stainless steel wire;
[0072] (2) The stainless steel wire coated in step (1) is aged at 240° C. for 1 h to obtain a rose slag activated carbon rod 2.
[0073] Example 6
[0074] (1) A stainless steel wire (1.0 cm*0.2 cm) was immersed in a hydrofluoric acid solution with a mass concentration of 30%, and after etching at 80° C. for 15 min, it was cleaned alternately with ultrapure water and anhydrous ethanol to obtain a rough surface with a certain diameter; a polyimide sealing resin was coated on the etched surface of the stainless steel wire, and the wire was quickly rolled back and forth on a weighing paper containing the rose dregs activated carbon material 1 prepared in Example 1, so that the rose dregs activated carbon material was evenly coated on the surface of the stainless steel wire;
[0075] (2) The stainless steel wire coated in step (1) is aged at 260° C. for 3 h to obtain a rose slag activated carbon rod 3.
[0076] Application Examples
[0077] The rose residue activated carbon in this application example is the rose residue activated carbon material 1 prepared in Example 1.
[0078] 1. Experimental methods
[0079] Add a certain amount of rose dregs activated carbon and a certain volume concentration of methylene blue solution into a centrifuge tube, put it into a multi-tube vortex mixer and oscillate at a rate of 2500r / min for 3 minutes, then put it into a low-speed multi-tube rack automatic balance centrifuge and centrifuge it at a rate of 5000r / min for 3 minutes before taking it out. Let the centrifuge tube stand at room temperature for adsorption, and measure the absorbance of the supernatant once every 1 hour using a UV-spectrophotometer based on the prepared methylene blue concentration standard curve, record the concentration of residual methylene blue in the supernatant every hour, and calculate the removal rate of methylene blue by rose dregs activated carbon.
[0080] The adsorption amount and removal rate of methylene blue by rose slag activated carbon can be calculated using the following two formulas:
[0081] μ=(C0-C1) / C0×100% (1)
[0082] ω=(C0-C1)×V / m (2)
[0083] Where:
[0084] μ is the removal rate of dye (%);
[0085] ω is the adsorption capacity of activated carbon (mg / g);
[0086] C0 is the initial concentration of methylene blue solution (mg / L);
[0087] C1 is the residual concentration of methylene blue after adsorption (mg / L);
[0088] m is the dosage of activated carbon (g);
[0089] V is the volume of the methylene blue solution (L).
[0090] 2. BBD central combination test design
[0091] The BBD central combination method was used to design the response surface experimental scheme for the prepared rose residue activated carbon, as shown in Table 1. According to the single factor experimental results of the adsorption of rose residue activated carbon, three factors that affect the adsorption performance of activated carbon (initial concentration of adsorbent, dosage of activated carbon, and solution pH) were selected and represented by A, B, and C respectively. Each factor took high, medium, and low levels, represented by -1, 0, and 1 respectively, that is, three factors and three levels. The removal rate of methylene blue was used as an evaluation index to optimize the adsorption process of rose residue activated carbon.
[0092] Table 1 Levels and influencing factors of response surface experimental design
[0093]
[0094] 3. Results and analysis
[0095] 3.1. Adsorption kinetics and adsorption isotherm analysis
[0096] 3.1.1. Adsorption kinetics analysis
[0097] 0.1g of rose dregs activated carbon was added to 40mL of 80mg / L methylene blue solution to study the kinetics of the adsorption of methylene blue by rose dregs activated carbon. The adsorption of methylene blue by rose dregs activated carbon was described by pseudo-first-order kinetics (Formula 3) and pseudo-second-order kinetics (Formula 4):
[0098] Ln(q e -q t ) = lnq e -k1t (3)
[0099] t / q t =1 / k2q e 2 +t / q e (4)
[0100] In the formula, q e and q t represents the adsorption capacity of methylene blue by rose dregs activated carbon at equilibrium and time t (mg·g -1 ), k1 represents the pseudo-first-order kinetic adsorption constant (min -1 ), k2 represents the pseudo-second-order kinetic adsorption constant [g·(mg·min) -1 ].
[0101] Origin 2021 software was used to perform nonlinear fitting of the experimental data using different kinetic models to obtain the kinetic parameters of the adsorption of methylene blue on rose dregs activated carbon (see Table 1 ). The adsorption kinetic fitting curve is shown in Figure 2 .
[0102] Table 2 Adsorption kinetic parameters
[0103]
[0104] As shown in the parameters in the table, the R 2 =0.964, R of pseudo-second-order kinetic model 2 =0.959, and the adsorption capacity of rose dregs activated carbon q was obtained by pseudo-first-order kinetics and pseudo-second-order kinetics models. e , both are close to the true value of 28.61 mg / g. It can be seen that both pseudo-first-order kinetics and pseudo-second-order kinetics can well describe the adsorption process of methylene blue by rose dregs activated carbon. However, due to the limitations of the pseudo-first-order model, that is, it can only describe the physical process of adsorption, and is often only suitable for the kinetic description of the initial stage of adsorption, but cannot accurately describe the entire process of adsorption. In contrast, the pseudo-second-order model includes all adsorption processes such as physical processes such as external liquid film diffusion, surface adsorption and intraparticle diffusion, as well as chemical processes such as surface complexation, ion exchange, and mineral co-precipitation. Therefore, the pseudo-second-order kinetic model is more suitable for describing the adsorption of methylene blue on the active sites of rose dregs activated carbon.
[0105] Depend on Figure 2 It can be seen that the adsorption of methylene blue by rose residue activated carbon is a rapid adsorption stage in the time period of 0 to 75 minutes. During this period, the activated carbon rapidly absorbs methylene blue, indicating that the surface of the activated carbon at this stage has abundant active sites, which can make the methylene blue be quickly absorbed; the slow adsorption stage is between 75 and 240 minutes. From this period, the absorption rate of methylene blue by activated carbon slows down, which means that most of the adsorption sites on the surface of activated carbon are occupied by methylene blue, but there is still a small part of the adsorption sites that are not occupied; after 240 minutes is an extremely slow absorption stage. During this period, the adsorption amount of methylene blue by activated carbon tends to be flat. At this time, the adsorption points on the activated carbon reach the adsorption saturation state, so the adsorption amount no longer increases with time.
[0106] 3.1.2. Adsorption isotherm analysis
[0107] 0.15 g of rose residue activated carbon was added to 40 ml of methylene blue solution with concentrations of 60, 80, 100, 120, 140, and 160 mg / L, respectively, and statically adsorbed for 4 hours at room temperature. The Origin 2021 software was used to select the Freundlich (Formula 5) and Langmuir (Formula 6) isothermal adsorption models for nonlinear fitting analysis of the experimental data.
[0108] q e =K F C1 / n (5)
[0109] q e =(q max K L Ce) / (1+K L Ce) (6)
[0110] Where: Ce is the equilibrium concentration of methylene blue, mg / L; q e is the equilibrium adsorption capacity of rose slag activated carbon for methylene blue, mg / g; q max is the theoretical maximum adsorption capacity of rose dregs activated carbon for methylene blue, mg / g; K F and K L are the Freundlich and Langmuir adsorption constants, respectively.
[0111] Figure 3 The Freundlich and Langmuir adsorption isotherm equations of rose dregs activated carbon for methylene blue adsorption are shown in Table 3. The isotherm parameters of rose dregs activated carbon for methylene blue adsorption are calculated by the nonlinear form of the Freundlich and Langmuir equations.
[0112] Table 3 Isotherm adsorption model parameters
[0113]
[0114] Freundlich and Langmuir's R 2 If both are greater than 0.9, then the Langmuir equation and the Freundlich equation can fit the isotherm of methylene blue adsorption on activated carbon well. Therefore, methylene blue has both monolayer adsorption and multilayer adsorption on the surface of activated carbon. 2 Higher than Langmuir's R 2 , indicating that the former is more suitable for describing the behavior of activated carbon in adsorbing methylene blue, and methylene blue is mainly adsorbed in multiple molecular layers on the surface of rose residue activated carbon.
[0115] 3.2. Recycling and regeneration of activated carbon
[0116] In order to further study the adsorption performance of rose dregs activated carbon, the prepared rose dregs activated carbon was recycled for 5 times. Figure 4As shown in the figure. The removal efficiency of activated carbon for methylene blue dye reached 94% and 87% in the second and third cycles respectively. After five cycles, the removal rate of methylene blue could still reach 73%. The results show that rose dregs activated carbon can be used as a reusable adsorbent with the potential to efficiently remove methylene blue dye. The reason why the adsorption effect gradually decreases with the number of cycles may be that the desorption of the reused activated carbon is incomplete and the active sites of the activated carbon are blocked after multiple uses.
[0117] 3.3. Single factor experimental results of activated carbon adsorption on methylene blue
[0118] 3.3.1 Effect of initial concentration of methylene blue on adsorption performance of activated carbon
[0119] Take 0.15g of rose flower residue activated carbon and add it to methylene blue solution of different concentrations. The removal rate of methylene blue is measured once every hour. The results of the change of the removal rate of methylene blue of different concentrations over time are shown as follows: Figure 5 As shown. Figure 5 It can be seen that with the increase of methylene blue concentration, the removal rate of methylene blue shows a downward trend. When the concentration of methylene blue increases from 60mg / L to 160mg / L, the removal rate of activated carbon for methylene blue reaches the maximum value at 4 hours of adsorption. At this time, the removal rate of activated carbon for 80mg / L and 60mg / L methylene blue solutions reaches 99% respectively.
[0120] After that, as the concentration of the methylene blue solution continued to increase, the removal rate of methylene blue began to decrease. This is mainly because at the beginning of adsorption, all the active sites in the rose slag activated carbon are empty. When added to the methylene blue solution with a high concentration, the concentration difference between the solid and liquid phases, that is, the adsorption power, is large, which leads to a rapid increase in the removal rate of methylene blue at the beginning. As the adsorption time increases, the active sites in the activated carbon are gradually occupied, and the concentration of methylene blue adsorbed by the activated carbon is low. At this time, the adsorption kinetics begins to decrease, and the adsorption rate reaches the maximum. When the adsorption time is >4 hours, the removal rates of methylene blue at different concentrations show a downward trend. When the initial concentration is 80 mg / L, the adsorption amount of rose slag activated carbon is 20.97 mg / g, which is much greater than the adsorption amount of rose slag activated carbon at 60 mg / L, which is 15.68 mg / g. Therefore, the initial concentration of methylene blue was selected as 80 mg / L for the subsequent experiments.
[0121] 3.3.2 Effect of activated carbon dosage on activated carbon adsorption performance
[0122] Weigh 0.05, 0.075, 0.1, 0.125, 0.15, and 0.175 g of rose slag activated carbon respectively and add them into 40 ml of 80 mg / L methylene blue solution. The removal rate of methylene blue is measured every hour. Figure 6 As shown in the figure, with the increase of activated carbon amount, the removal rate of methylene blue showed an increasing trend.
[0123] Depend on Figure 6 It can be seen that the dosage of activated carbon has a significant effect on the removal rate of methylene blue. When the dosage of activated carbon is 0.15g, the removal rate of methylene blue reaches a maximum value of 99.99%. This is because when the dosage of activated carbon is less than 0.15g, as the dosage of activated carbon increases, the pore size and functional groups of activated carbon increase, the better the adsorption of methylene blue, the greater the removal rate. When the dosage>0.15g, the removal rate of methylene blue begins to decline when>4h. This is because when the dosage is large enough, the concentration of methylene blue in the solution is relatively very low, and a large amount of activated carbon and methylene blue do not have adsorption, and the dosage has exceeded the optimal dosage. In addition, there is no significant difference in the removal rate of methylene blue when the dosage is 0.15g and 0.175g. Considering the saving of activated carbon, the dosage of activated carbon selected in the subsequent experiment is 0.15g.
[0124] 3.3.3 Effect of initial solution pH on the adsorption performance of activated carbon
[0125] 0.15 g of rose slag activated carbon was added to 40 ml of 80 mg / L methylene blue solution with pH adjusted to 3, 5, 7, 9, 11, and 13, respectively. The removal rate of methylene blue was measured once every hour, and the effect of the initial pH of the methylene blue solution on the removal rate of methylene blue was analyzed. Figure 7 shown.
[0126] Depend on Figure 7 It can be seen that the removal rate of methylene blue reaches a maximum of 97.97% after 4 hours of adsorption at pH = 13, and the removal rate is 95.13% when pH = 3. This shows that the adsorption of methylene blue in water by rose dregs activated carbon has a wide pH application range and can be used to remove methylene blue from wastewater with different pH values. In addition, the adsorption effect in alkaline solution is slightly stronger than that in acidic solution. The reason may be that when pH < 7, H + There is competition with methylene blue for the adsorption sites of activated carbon. As the pH value increases, H + As the number of active sites decreases, the activated carbon will have enough active sites to adsorb methylene blue.
[0127] 3.4. Response surface optimization results of rose slag activated carbon
[0128] 3.4.1. Response surface experimental design optimization results
[0129] Based on the Box-Behnken model in the statistical software Design Expert 13.0, the three influencing factors in the table were experimentally designed. The experimental results are summarized in the table.
[0130] Table 4 Experimental design and response values based on Box-Behnken model
[0131]
[0132]
[0133] Note: 6, 7, and 14 in the table are the removal rates of methylene blue by rose residue activated carbon under the same adsorption conditions. The experiment was repeated three times mainly to evaluate the impact of random errors on the accuracy of the regression model.
[0134] 3.4.2 Analysis of experimental design results
[0135] Design-experts13.0 software was used to perform multivariate fitting on the methylene blue removal rate response values in the table, and the regression equation was established: Q = 99.66 + 1.93A-1.62B + 0.0075C + 0.0425AB-0.3775AC + 0.2225BC-2.3A 2 -1.43B 2 -1.35C 2 .
[0136] In the formula, Q is the removal rate of methylene blue (%), A is the initial concentration of methylene blue (mg / L), B is the dosage of activated carbon (g), and C is pH. According to the above regression equation, the removal rate of methylene blue under the corresponding experimental conditions was predicted respectively, and the comparison between the predicted value and the experimental value is shown in Figure 8 ,Depend on Figure 8 It can be seen that the predicted values are in good agreement with the experimental values.
[0137] As shown in Table 5, the significance of the fitting equation was tested by analysis of variance (ANOVA). The results of the variance analysis showed that the f value obtained by the model test was 72.49, indicating that the model was sufficiently significant (P<0.0001). The probability of obtaining this "model f value" due to model error is less than 0.01%. The p value is usually used to test the significance of model terms. The smaller the p value, the more significant the corresponding model term. In this experiment, A, B, A 2 , B 2 , C 2 are significant model terms (all p values are significant < 0.05).
[0138] Table 5 Variance analysis table
[0139]
[0140]
[0141] In addition, the p value of AC is close to 0.05, which is also slightly significant. From the F value and P value, it can be seen that the influence degree on the removal rate of methylene blue is from large to small, which is the dosage of activated carbon, the concentration of methylene blue, and pH.
[0142] From Table 6, we can see that the R 2 =0.9924, indicating that the model can explain 99% of the response surface value changes in this experiment, and the fitting is good, proving that it is feasible to use the response surface method to optimize the adsorption of methylene blue by rose dregs activated carbon, and the model is meaningful. 2 and Pred R 2 The closer the two values are, the closer the experimental data are to the predicted values. In this experiment, the difference between the two is less than 0.2, which proves that the predicted value of the model is consistent with the measured value. CV is the coefficient of variation, which is mainly used to measure the accuracy of experimental data. In this experimental data, CV = 0.36% < 10%, Adeq Precision = 25.4003 > 4, which proves that the model has high accuracy and credibility for this experiment.
[0143] Table 6 R of regression equation 2 and standard deviation analysis
[0144]
[0145] 3.4.3 Impact of the interaction of various factors
[0146] The three-dimensional response surface plot is very suitable for studying the main effects of independent variables and the interactions between factors. On this basis, RSM was used to further analyze the interactions and optimal levels of the three influencing factors in improving the removal efficiency of methylene blue. Figures 9 to 11 The response surface and contour map of the interaction of various factors on the removal rate of methylene blue. If the contour lines are elliptical, it means that the interaction between the two is significant, and if they are circular, it means that the interaction between the two is weak. The greater the density of the contour lines, the more significant the influence of the corresponding factors.
[0147] Depend on Fig. 9 It can be seen that at a certain pH, the combined effect of the initial concentration of methylene blue and the dosage of activated carbon on the removal rate of methylene blue was investigated. Fig. 9The interaction effect is the most significant, which is consistent with the results of the variance analysis of the model. With the increase of the dosage of activated carbon and the initial concentration of methylene blue, the removal rate of methylene blue will increase first and then decrease, and the contour line at this time is elliptical. Under the coupling effect of pH and the dosage of activated carbon, the removal effect of rose dregs activated carbon on methylene blue is more significant ( Fig.10 ), the contour lines are also elliptical. Fig.11 The results of variance analysis show that the interaction between pH and initial concentration of methylene blue has a weaker influence on the removal rate of methylene blue, and the contour lines are circular.
[0148] The optimal adsorption conditions of rose dregs activated carbon for methylene blue were predicted by response surface experiment: the dosage of activated carbon was 0.153g, the initial concentration of methylene blue was 64.35, and the pH was 10.93. Under these conditions, the removal rate of methylene blue was predicted to reach 100%. In order to verify the reliability of the model, the experimental parameters were set as the optimal parameters predicted by the model. The experimental results showed that under these conditions, the removal rate of methylene blue by rose dregs activated carbon reached 99.94%, and the relative error with the model prediction was within 5%. This shows that the model can well predict the removal effect of rose dregs activated carbon on methylene blue, and it also shows that the method of optimizing the adsorption of methylene blue by rose dregs activated carbon using response surface methodology is feasible.
[0149] 3.5 Characterization results analysis
[0150] 3.5.1. Specific surface area and pore size analysis
[0151] The pore size and distribution of rose slag activated carbon were analyzed by pore size analyzer. The nitrogen adsorption and desorption isotherms and pore size distribution are shown in Figure 2. Fig.12 As shown by Fig.10 It can be seen that the adsorption-desorption isotherm of rose residue activated carbon belongs to type IV, and the characteristic of type IV isotherm is its hysteresis loop.
[0152] When p / p0<0.1, the adsorption amount increases rapidly, indicating that the rose dregs activated carbon has a microporous structure; when p / p0<0.2-0.5, the adsorption amount increases slowly, indicating that the pore structure of the rose dregs activated carbon is relatively stable and has a mesoporous structure. Observing the pore size distribution of the rose dregs activated carbon, it can be seen that the pore size of the activated carbon is concentrated between 2 and 6 nm. According to the BET method, the average pore size of the activated carbon is 4.2 nm, and the total pore volume is 0.1589 cm 3 / g, and the proportion of mesopores is 54.05%, which means that the main structure is mesopores, and there are a small number of micropores and macropores. The more concentrated pore structure can provide a specific surface environment for the adsorption of activated carbon and increase the active sites of the catalytic reaction.
[0153] 3.5.2 SEM analysis
[0154] The microscopic morphology of rose dregs and activated carbon was visually displayed by scanning electron microscopy. Fig.13 As shown, rose slag can be seen in the SEM image ( Fig.13 a) has a blocky structure on its surface, or a lamellar structure with almost no obvious pores. Fig.13 b) The surface shows obvious pore structure, and the pore shape is a neatly arranged honeycomb structure. This is because KOH enters the structure during activation and acts as a carbon skeleton to form a porous structure. In addition, due to the impregnation of KOH, the heterogeneous pore structure of rose slag activated carbon increases. The development of this surface morphology is conducive to the adsorption process on the surface of activated carbon.
[0155] 3.5.3 Elemental analysis
[0156] The elemental analysis of the rose flower residue activated carbon is shown in Table 7. There are three main elements: C (67.28%), N (1.52%), and O (19.59%). The percentages of other elements (sodium, silicon, aluminum, calcium, magnesium, sulfur, iron, aluminum, phosphorus, and potassium) detected in the activated carbon are relatively low (<5%) (e.g. Fig.14 As shown). It can be seen that the main component of rose slag activated carbon is C element, mainly C-containing functional groups. In addition to the carbon skeleton containing C, there is obviously a small amount of O element distribution. C and O elements are the most important elements affecting the surface performance and activity of activated carbon, and their total accounts for 86.78%. The activation of potassium hydroxide increases the mass fraction of O on rose slag activated carbon. The increase of these C, O, and N functional groups will increase the adsorption sites of rose slag activated carbon. In addition, (N+O) / C shows that rose slag activated carbon has certain polarity and aromaticity, which further improves the adsorption performance of rose slag activated carbon.
[0157] Table 7 Physical and chemical properties of rose slag activated carbon
[0158]
[0159] 3.5.4 XRD analysis
[0160] XRD diffraction analysis can detect the phase shape and crystal structure of rose residue activated carbon samples. The chemical state of the activated carbon material can be obtained based on the information in the diffraction spectrum. It is an effective method for qualitative analysis of crystal structure.
[0161] XRD was used to characterize the structural properties of rose slag activated carbon. Fig.15As shown. Due to the diffraction of carbon structure and crystal plane, there are four obvious peaks in the XRD spectrum of rose dregs activated carbon, which are at 2θ=11.26, 19.3, 26.78 and 31.82 respectively, which indicates that rose dregs activated carbon has a shaped and ordered crystalline structure, and that the crystal structure of rose dregs activated carbon is more obvious.
[0162] 3.5.5 Fourier transform infrared spectroscopy analysis
[0163] Fourier transform infrared spectroscopy is a useful tool for identifying functional groups on the surface of activated carbon. Many heteroatoms, including oxygen, hydrogen, nitrogen, etc., can exist as single atoms or functional groups on the porous carbon surface. FTIR analysis was used to observe the organic and inorganic functional groups on the surface of the prepared rose dregs activated carbon. The spectral model was used at 4000-500 cm -1 The surface chemical properties of porous carbon were studied in the range of Fig.16 The surface functional groups of rose residue activated carbon are recorded in Table 8.
[0164] Table 8 FTIR spectral characteristics of rose slag activated carbon surface
[0165]
[0166] from Fig.14 It can be seen that the rose slag activated carbon is at 3123cm -1 The absorption peaks on the left and right correspond to the stretching vibration peaks of OH and NH; 2362cm -1 The absorption peak of 1399cm is due to the stretching vibration of C≡C. -1 The absorption peaks near 500-1250cm may belong to the stretching vibration of OH and CH. -1 There are some small absorption peaks in the interval, corresponding to the stretching vibrations of CC, CH and other skeletons. This is because rose dregs contain lignin and cellulose, and activated carbon causes cellulose to be destroyed due to activation, so there is no absorption peak in this interval. From the above analysis, it can be seen that rose dregs activated carbon has significantly fewer functional groups, and the functional groups it contains are mainly carboxyl and carbonyl hydrophilic groups, which are conducive to the adsorption reaction.
[0167] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing rose slag activated carbon rods, characterized in that: The method comprises the following steps: (A) After coating the etched stainless steel wire surface with polyimide sealing resin, rose slag activated carbon is quickly and evenly coated on the stainless steel wire surface; (B) aging the coated stainless steel wire in step (A) at 240-260° C. for 1-3 h to obtain a rose slag activated carbon rod; The preparation method of the rose slag activated carbon comprises the following steps: (1) Carbonizing the dried rose dregs at 230-250°C for 6-8 minutes to obtain a carbon precursor; (2) impregnating the carbon precursor in the activator for 3 to 5 hours to obtain an impregnation solution; (3) adding the impregnation liquid into a high-temperature muffle furnace preheated to 390-410°C, heating the furnace to an activation temperature of 490-510°C at a rate of 9-11°C / min, maintaining the activation temperature for 45-55 min, then taking the furnace out and cooling it to room temperature to obtain an activated product; (4) The activated product is sequentially acid-washed, water-washed and dried to obtain rose residue activated carbon.
2. The method according to claim 1, characterized in that In step (1), the dried rose flower residue is carbonized at 240° C. for 7 min to obtain a carbon precursor; In step (2), the activator is potassium hydroxide with a mass concentration of 20%, and the impregnation ratio of the carbon precursor in the activator is 1:
1.
3. The method according to claim 1, characterized in that In step (3), the impregnation liquid is added into a high-temperature muffle furnace preheated to 400°C, and the temperature is raised to an activation temperature of 500°C at a rate of 10°C / min. After being kept at the activation temperature for 50 minutes, the impregnation liquid is taken out and cooled to room temperature to obtain an activated product.
4. The method according to claim 1, characterized in that In step (4), the acid washing is to use a hydrochloric acid solution with a mass concentration of 10% until no reaction occurs after the addition of the acid; the water washing is to use water until the outflowing water is transparent and colorless; the drying is to dry at 110°C for 3 hours, then take out and cool to room temperature.
5. The method according to claim 1, characterized in that In step (A), the stainless steel wire is immersed in a hydrofluoric acid solution with a mass concentration of 40%, etched at 70° C. for 10 minutes, and cleaned alternately with ultrapure water and anhydrous ethanol to obtain a stainless steel wire with a rough surface after etching.
6. Rose residue activated carbon rod prepared by the method according to any one of claims 1 to 5.
7. Application of the rose slag activated carbon rods as claimed in claim 6 in adsorbing wastewater dyes; wherein, The dyes include methylene blue, methyl orange, rhodamine B, malachite green or crystal violet.
8. The use according to claim 7, characterized in that The dye is methylene blue.
Citation Information
Patent Citations
Mangnolia petal biological carbon of loose and porous structure and preparation method thereof
CN106608627A
Olive pomace activated carbon, preparation method thereof and methylene blue removal method
CN116789133A